Проблеми розвитку вищої освіти в Україні: соціально-філософський аспект - Ісакова, Олена Іванівна; Исакова, Елена Ивановна; Isakova, Olena; Баєва, О. (My University, 2020)
UK: Робота являє собою соціально-філософський аналіз проблем розвитку вищої освіти. Звернення до дослідження проблем розвитку освіти зумовлено необхідністю вдосконалення вищої освіти, щоб освіта відповідала сучасним запитам суспільства і особистості, актуальним ціннісним орієнтаціям світової спільноти. Для цього необхідна модернізація форм і методів освітньої діяльності і вироблення нових орієнтирів освіти. Освіта стає одним з головних механізмів еволюції цивілізації. Саме освіта, в зміст якої включені нові соціально-філософські домінанти, має підготувати перехід людства на шлях регульованого розвитку, здійснити якість можливе лише за умови радикальної зміни масової свідомості і перш за все ціннісних орієнтацій більшості людей на нашій планеті. І в цьому плані мета освіти — формувати суспільний інтелект, етичний сукупний розум, відповідний до концепції регульованого світового розвитку Для того щоб освіта стала джерелом нових ідей і середовищем, де формується відповідальне мислення особистість зможе реалізувати себе, де молоде покоління долучається до нового бачення світу, де культивуються нові погляди і ціннісні орієнтації, необхідні ревізія і подальша модернізація цілей, змісту, форм і методів освіти. Мета дослідження-розкрити соціально-філософські підстави проблем вищої освіти в Україні та особливості сучасної освітньої парадигми як важливої теоретичної передумови реформування освітньої системи. Аналіз сучасних визначень цілей освіти дозволяє виділити в них спільне: освіта повинна бути спрямована не тільки на розвиток інтелекту і професійних якостей, але, в першу чергу, на розвиток духовності людини: височини думки, відповідальності, почуття обоє ’язку, людинолюбства. Освіта розглядається як простір, в якам створєні умови для саморгалізації особистості, для пізнання людиною самої себе. На фундаментальному рівні освіта повинна розглядатися як феномен культури, як її підсистема і механізм еволюції в динаміці, на антропологічному рівні необхідні дослідження еволюції людської свідомості, соціальних ментальностей в культурно-освітніх середовищах, на прикладному — розробка технологій модернізації освітньої сфери відповідно до закономірностей культурної еволюції і сучасного культурного етапу. EN: The work is a socio-philosophical analysis of the problems of the development of higher education. The appeal to the study of the problems of education development is due to the need to improve higher education so that education meets the modern needs of society and the individual, and corresponds to the current value orientations of the world community. This requires the modernization of forms and methods of educational activities and the development of new guidelines for education. Education is becoming one of the main mechanisms of the evolution of civilization. It is education, in the content of which new socio-philosophical dominants are included, that should prepare the transition of mankind to the path of regulated development, which can only be realized under the condition of a radical change in mass consciousness and, above all, in the value orientations of most people on our planet. And in this regard, the goal of education is to form social intelligence, an ethical aggregate mind, corresponding to the concept of regulated world development. In order for education to become a source of new ideas and an environment where responsible thinking is formed, where a person can realize himself, where the younger generation joins a new vision of the world, where new views and value orientations are cultivated, corresponding to regulated (controlled) world development, revision and subsequent modernization of goals, content, forms and methods of education. The purpose of the study is to reveal the socio-philosophical foundations of the problems of higher education in Ukraine and the features of the modern educational paradigm as an important theoretical prerequisite for reforming the educational system. An analysis of various modern definitions of the goals of education allows us to single out the general in them: education should be aimed not only at the development of intelligence and professional qualities, but, first of all, at the development i of human spirituality: the loftiness of thought, responsibility, sense of duty, sensitivity and tolerance, philanthropy. Education is viewed as a space in which conditions have been created for the self-realization of the individual, for the person to know himself, for the development of the student’s individual lifestyle and activity. At the fundamental level, education should be considered as a phenomenon of culture, as its subsystem and mechanism of evolution in dynamics, at the anthropological level it is necessary to study the evolution of human consciousness, social mentality in cultural and educational environments, at the applied level — to develop technologies for the modernization of the educational sphere in accordance with the laws of cultural evolution and modern cultural stage.
Problems of development of higher education in Ukraine: social and philosophical aspect
Keywords: вища освіта; гуманізація; модернізація освіти; безперервна освіта; Higher education; humanization; modernization of education; continuing education